LİPOMATÖZ TÜMÖR SERİMİZİN DAĞILIMI VE YENİ TANIMLANAN LİPOMATÖZ TÜMÖRLER - ÜSTÜNDAĞ, Nil; Dervişoğlu, Sergülen (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Lipomatous tumors make up the largest group of the mesenchymal tumors. In the past ten years significant changes have been made on the classification of the lipomatous tumors. In this report, we aimed to evaluate the histopathological and clinical aspects of lipomatous tumors diagnosed at our department between 1988 and 1999 according to these changes. Methods.- Lipomatous tumors diagnosed at Istanbul University Cerrahpasa Faculty of Medicine between 1988 and 1999, have been classified according to Enzinger and Weiss’ classification. The cases were evaluated by age, sex, localization average diameter, largest diameter and multiplicity criteria. Results.- Out of the 843 lipomatous tumors, 799 were benign and 44 were malignant. 630 cases were classified as lipoma (75%), 83 cases as angiolipoma (10%), 52 cases as fibrolipoma (6%), 11 cases as infiltrating lipoma (1,3%), 10 cases as spindle cell lipoma (1%), 2 cases as giant lipoma (0,2%), 2 cases as angiomyolipoma (0,2%), 3 cases as lipoblastoma (0,3%), 1 case as plemorphic lipoma (0,1%), 1 case as myxolipoma (0,1%), 1 case as atypic lipoma (0,1%) and 1 case as myolipoma (0,1%). All groups showed correlation with the literature for the criteria of age, sex, localization, average diameter, largest diameter and multiplicity. Number of cases of simple lipomas with multiple location was similar with that of Enzinger’s series. The maximum diameter and infiltrative margin in spindle cell lipomas, and maximum diameter in angiolipomas differed from the current literature. Recently described entities were discussed.